Sequence variation in PPP1R13L results in a novel form of cardio‐cutaneous syndrome - Tzipora C Falik‐Zaccai; Yiftah Barsheshet; Hanna Mandel; Meital Segev; Avraham Lorber; Shachaf Gelberg; Limor Kalfon; Shani Ben Haroush; Adel Shalata; Liat Gelernter‐Yaniv; Sarah Chaim; Dorith Raviv Shay; et al. (EMBO Molecular Medicine)
Abstract Dilated cardiomyopathy (DCM) is a life‐threatening disorder whose genetic basis is heterogeneous and mostly unknown. Five Arab Christian infants, aged 4–30 months from four families, were diagnosed with DCM associated with mild skin, teeth, and hair abnormalities. All passed away before age 3. A homozygous sequence variation creating a premature stop codon at PPP1R13L encoding the iASPP protein was identified in three infants and in the mother of the other two. Patients’ fibroblasts and PPP1R13L‐knocked down human fibroblasts presented higher expression levels of pro‐inflammatory cytokine genes in response to lipopolysaccharide, as well as Ppp1r13l‐knocked down murine cardiomyocytes and hearts of Ppp1r13l‐deficient mice. The hypersensitivity to lipopolysaccharide was NF‐κB‐dependent, and its inducible binding activity to promoters of pro‐inflammatory cytokine genes was elevated in patients’ fibroblasts. RNA sequencing of Ppp1r13l‐knocked down murine cardiomyocytes and of hearts derived from different stages of DCM development in Ppp1r13l‐deficient mice revealed the crucial role of iASPP in dampening cardiac inflammatory response. Our results determined PPP1R13L as the gene underlying a novel autosomal‐recessive cardio‐cutaneous syndrome in humans and strongly suggest that the fatal DCM during infancy is a consequence of failure to regulate transcriptional pathways necessary for tuning cardiac threshold response to common inflammatory stressors.